Improving the efficiency of sanitation of urological catheters with various types of exposure to ultrasound emitters - A. A. Novikov; A. R. Putintseva (Омский научный вестник)
The purpose of the article is to determine rational modes for safe and effective ultrasound exposure in order to sanitation urological catheters. It is shown that using an amplitude-modulated or pulsed power supply mode, it is possible to achieve an increase in amplitude, i.e. to improve the quality of cleaning and reduce heat generation. As a result, to technological solutions for the initiation of an ultrasonic emitter have been proposed.